Structure and floristic composition of the medium subdeciduous forest in Hobomó, Campeche, Campeche, Mexico - Zamora-Crescencio, Pedro; Barrientos Medina, Roberto Carlos; Plasencia-Vázquez, Alexis Herminio; Villegas, Pascale; Domínguez-Carrasco, María del Rosario; Gutiérrez-Báez, Celso; Aguirre-Crespo, Francisco Javier; Vargas-Contreras, Jorge Albino; Uc-Ruvalcava, Samuel; Poot Sarmiento, Itzel Guadalupe (Instituto de Ecología, A.C., 2020)
We studied species the composition and structure in two sites of the subdeciduous tropical forest in Hobomó, Campeche, Mexico. We analyzed 10 plots of 10 m2 × 10 m2 (1000 m2), in each site, where all individuals with a diameter ≥ 1 cm were measured. Vegetation structure was characterized using the importance values of the species, and species diversity was estimated with the Shannon-Wiener (H’) Index. A total of 79 species, representing 67 genera and 30 families, was recorded. The most diverse families were Fabaceae and Rubiaceae at the two sites. The most diverse genus was Diospyros, followed by Coccoloba and Guettarda. The diversity of woody species in the study sites were 3.68 and 3.59 in site one and site two, respectively, while their corresponding evenness values (according to Pielou’s index) were 0.88 and 0.87, respectively. The mean densities of the woody species encountered in the sites one and two were 6610 ind/ha and 8670 ind/ha, respectively. The three species with the greatest density were Malpighia glabra, Guettarda combsii and Lonchocarpus xuul in site one, and Machaonia lindeniana, Coccoloba cozumelensis and Malpighia glabra in site two. The highest values of importance value index were Bursera simaruba, Lonchocarpus xuul, Guettarda combsii, Platymisium yucatanum and Malpighia glabra in site one and   Lysiloma latisiliquum, Bursera simaruba, Vitex gaumeri, Lonchocarpus xuul y Machaonia lindeniana in site two. These species are the most important in the structure and physiognomy of the community. We can conclude that the richness of the tree species of the two sites studied its similar (site 1with 63 spp. and site two with 62 spp.). The scarcity or abundance of the species is related to human activity (wood extraction), which affects the structure and floristic composition.